TANTANGAN DAN STRATEGI GURU DALAM MENGIDENTIFIKASI KESULITAN BELAJAR "DISLEKSIA" DI SEKOLAH DASAR - Nurdiantika, Emalia; Febriani, Diva; Handayani, Yuslia Vera; Minsih, Minsih (JPI (Jurnal Pendidikan Inklusi), 2022)
In the educational process at school, various obstacles often arise, especially when some students experience difficulties in achieving the expected level of achievement. One common issue is learning disabilities, such as reading difficulties. The success of students in following the learning process is greatly influenced by their reading abilities. Therefore, the role of teachers is crucial in improving students' reading skills. This research involves teachers and students with dyslexia. Data collection methods include participatory observation, in-depth interviews, documentation, and triangulation. The research results show that: (1) causes of dyslexia include internal and external factors; internal factors include psychological and physiological aspects, while external factors include family, school, and community environments; (2) challenges faced by teachers in identifying dyslexia include time constraints, difficulties in differentiation, limited support services, and communication challenges with students' parents; (3) teacher strategies in dealing with dyslexia include using supportive teaching methods, providing additional time, and offering supportive motivation.